2016
DOI: 10.1093/infdis/jiw605
|View full text |Cite
|
Sign up to set email alerts
|

Long-term durability of responses to 2 or 3 doses of hepatitis A vaccination in HIV-positive adults on antiretroviral therapy

Abstract: Three doses versus 2 doses of HAV vaccine improve the durability of immune responses in terms of higher concentrations of specific IgG, which take longer to decay to subthreshold levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 30 publications
0
43
2
1
Order By: Relevance
“…In HIV-positive individuals, a slight decrease was observed over time; 88.6%-100% of responders were still seroprotected after 1 year[115,120], 86.8%-90% after 3 years[135,136], 85%-85.4% after 4 years[136,137], and 75.5%-88.4% after 5 years[135,136,138]. Percentages of seroprotection at the end of 5 years of follow-up were 78.9% vs 76.4% by ITT analysis ( p = 0.61) (Table 8)[135-138].…”
Section: Hav Vaccination and Factors Associated With Immunogenicity Amentioning
confidence: 99%
See 1 more Smart Citation
“…In HIV-positive individuals, a slight decrease was observed over time; 88.6%-100% of responders were still seroprotected after 1 year[115,120], 86.8%-90% after 3 years[135,136], 85%-85.4% after 4 years[136,137], and 75.5%-88.4% after 5 years[135,136,138]. Percentages of seroprotection at the end of 5 years of follow-up were 78.9% vs 76.4% by ITT analysis ( p = 0.61) (Table 8)[135-138].…”
Section: Hav Vaccination and Factors Associated With Immunogenicity Amentioning
confidence: 99%
“…Percentages of seroprotection at the end of 5 years of follow-up were 78.9% vs 76.4% by ITT analysis ( p = 0.61) (Table 8)[135-138]. GMTs were significantly higher throughout each consecutive year with the 3-dose schedule as compared to the standard 2-dose schedule[136]. Factors associated with persistent seroprotection include virologic suppression at vaccination and maintained lower levels of HIV viremia as denoted by time-updated plasma HIV RNA load[135,137], 3-dose compared to 2-dose schedule (adjusted odds ratio 3.36; 95%CI: 1.14-9.93), acute syphilis and absence of acute hepatitis C[136,138].…”
Section: Hav Vaccination and Factors Associated With Immunogenicity Amentioning
confidence: 99%
“…The retrospective design of our study of a shorter observation duration and the natural booster effect that might occur during an ongoing HAV outbreak may have contributed to the discrepancies observed. Another potential explanation could be that the population in our study was mostly virally suppressed and had higher baseline CD4 lymphocyte counts compared to those included in the previous studies . Of note, the sample size of the current study was 5 times as large as the two previously mentioned studies combined.…”
Section: Discussionmentioning
confidence: 80%
“…Although seroreversion cannot be translated directly into loss of protection, as shown in the anamnestic response after hepatitis B vaccination, AHA in HIV‐positive individuals who had had positive anti‐HAV antibodies has been reported, indicating that loss of seroprotective antibodies may lead to susceptibility to hepatitis A infection in the HIV‐positive population. Several studies reported a substantial rate of loss of HAV antibodies after vaccine‐induced seroconversion . Launay et al and Cheng et al, in their previous investigations, found that, at 18 months after vaccination, seroreversion rates were 6% and 13%, respectively .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation